2012
DOI: 10.1186/1471-2407-12-333
|View full text |Cite
|
Sign up to set email alerts
|

Expression of S100A4, ephrin-A1 and osteopontin in non-small cell lung cancer

Abstract: BackgroundThe metastasis-promoting protein S100A4 induces expression of ephrin-A1 and osteopontin in osteosarcoma cell lines. The aim of this study was to investigate S100A4-mediated stimulation of ephrin-A1 and osteopontin in non-small cell lung cancer (NSCLC) cell lines, and to characterize the expression of these biomarkers in primary tumor tissue from NSCLC patients.MethodsFour NSCLC cell lines were treated with extracellular S100A4, and ephrin-A1 and osteopontin expression was analyzed by real time RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…S100A4 is often overexpressed in NSCLC as well as other tobacco-related malignancies, making it an excellent therapeutic target for lung and other cancers. As published in other reports [23, 24], we found that S100A4 expression was elevated in lung adenocarcinoma. However, due to the small sample size and lack of non-smokers in our population, we could not confirm an association between S100A4 expression and tobacco exposure.…”
Section: Discussionsupporting
confidence: 89%
“…S100A4 is often overexpressed in NSCLC as well as other tobacco-related malignancies, making it an excellent therapeutic target for lung and other cancers. As published in other reports [23, 24], we found that S100A4 expression was elevated in lung adenocarcinoma. However, due to the small sample size and lack of non-smokers in our population, we could not confirm an association between S100A4 expression and tobacco exposure.…”
Section: Discussionsupporting
confidence: 89%
“…Among them, S100A4, a member of the S100 family, was positively regulated by LASP1 in colorectal cancer cells. S100A4 was overexpressed in several kinds of tumor, including gastric (23), hepatocellular (24), colorectal (25), lung (26), and breast carcinoma (27). This was recognized as colorectal cancer metastasis-associated protein and represented as a highly significant prognostic marker in colorectal cancer (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulated OPN induces increased expression of GLUT1 and GLUT3 resulting in enhanced glucose uptake into hypoxic OS cells via the avb3 integrin which is responsible for the OS cell proliferation and drug resistance [25]. OPN is a downstream effector of S100A4 (the metastasis-promoting protein) which induces a variety of cellular effects including stimulation of angiogenesis, regulation of cell death, increased cell motility, invasion and metastasis [37,38]. Extracellular S100A4 is reported to stimulate the secretion of OPN, and increased level of OPN induces up-regulation of the components of the plasminogen activator system (uPA and its receptor uPAR) as well as matrix metalloproteinases (MMPs) by activating the transcription factor NF-kappaB in OS cell lines through induction of phosphorylation and subsequent degradation of the NF-kappaB inhibitor, IjBa.…”
Section: Role Of Osteopontin In Osteosarcoma Pathogenesismentioning
confidence: 99%